Advances and obstacles of T cell-based immunotherapy in gynecological malignancies - Zhao, Xi; Ran, Jialing; Li, Shenglong; Chen, Jinxin (Molecular cancer, 2025)
T cell-mediated immunotherapy has revolutionized oncology by enabling precision immune responses against malignant cells. Chimeric Antigen Receptor (CAR) T-cell therapy, which involves genetically reprogramming T lymphocytes to recognize tumor-specific antigens, has shown clinical success in hematologic malignancies and is expanding its potential in solid tumors. Gynecological cancers, including ovarian, cervical, and endometrial carcinomas, present persistent therapeutic challenges due to their aggressive recurrence patterns and limited responses to conventional therapies in advanced disease stages. This review offers a comprehensive analysis of CAR-T cell therapy advancements in gynecologic oncology, examining fundamental biological mechanisms of tumor-immune interactions, clinical progress in target antigen validation, and innovative approaches to counter immunosuppressive tumor microenvironments. Key challenges specific to these malignancies are discussed, such as molecular heterogeneity in endometrial tumors, ascites-mediated T-cell dysfunction in ovarian cancer (OC), and viral antigen dynamics in HPV- driven cervical carcinomas. Recent clinical evidence shows improved therapeutic outcomes through optimized CAR architectures and preconditioning regimens, with objective response rates demonstrating progressive enhancement across successive clinical trial generations. The discussion addresses ongoing limitations regarding treatment durability and manufacturing consistency while exploring emerging solutions such as synthetic biology approaches and multi-omics guided antigen selection. By integrating preclinical insights with translational clinical data, this work establishes a strategic framework for advancing adoptive T-cell therapies in gynecologic oncology, emphasizing the synergistic potential of combining CAR-T technology with personalized neoantigen vaccines and microenvironment-reprogramming agents. These collective advances underscore the transformative prospects of engineered T-cell immunotherapies while providing actionable strategies to overcome the unique biological barriers inherent to female reproductive tract malignancies.